Adenocarcinoma in the columnar epithelial lined lower (Barrett) oesophagus. Issue 4 (July 1973) - Hawe, Anthony; Payne, W. Spencer; Weiland, Louis H.; Fontana, Robert S.
Abstract : Hawe, A., Payne, W. S., Weiland, L. H., and Fontana, R. S. (1973). Thorax, 28, 511-514. Adenocarcinoma in the columnar epithelial lined lower (Barrett) oesophagus. At the Mayo Clinic, five patients with Barrett oesophagus developed adenocarcinoma of the oesophagus at sites cephalad from the anatomic cardia but separated from it by a definite segment of columnar lined oesophagus. Twelve similar cases have been reported in the literature, including one from this institution. Of 85 Mayo Clinic patients in whom a clinical diagnosis of benign Barrett oesophagus was made in the 20-year period 1950-69, two subsequently developed oesophageal cancer. Since its description in 1950 by Barrett, the columnar epithelial lined lower oesophagus has been encountered with increasing frequency. The full clinical implications of this unusual condition are only partially appreciated at this time, and the present report, as well as previous ones, suggest that the condition may be premalignant.